Enhanced intersystem crossing to achieve long-lived excitons based on inhibited molecular motion and rigid structure. (February 2020) - Kong, Lin; Huang, Ze; Chen, Pengfei; Wang, Haiyan; Zhu, Shujuan; Yang, Jiaxiang
Abstract: Two cyanyl-carboxylic derivatives (PYCZA and TPYCZA ) have been designed and synthesized with flexible or rigid substituents, respectively. The persistent phosphorescence mechanism was studied through temperature-dependent Raman spectroscopy, and single/powder X-ray diffraction. The low temperature shortened intermolecular distance and enhanced intermolecular interactions, fluorescence emission (1.5 fold for TPYCZA, 1.6 fold for PYCZA ) and the luminescent lifetime (1.23 × 10 7 fold for TPYCZA, 1.43 × 10 9 fold for PYCZA ). The results provide a fundamental basis for the design of organic molecules with extended luminescence lifetimes, which broadens the scope for phosphorescent materials with thermochromic properties. Graphical abstract: Image 1 Highlights: The two cyanyl-carboxylic derivatives with long luminescence lifetimes of up to 228 ms for PYCZA and 88 ms for TPYCZA. Raman spectroscopy and PXRD reveal inhibited molecular vibration and closer molecular packing. The as-revealed key influence of the molecular motion suppress nonradiative transition for phosphorescence emission.